Coping with stress - Salmaani Barough N; Taghavi Larijani T; Monjamed Z; Sharifi N; Bahrani N (Tehran University of Medical Sciences, 2004)
Introduction: Stress is a complex and physiologic phenomenon that sometimes can be a source of problem. If an individual could not cope with stress, it would be a threat to physical and psychological health. Inclination to cope with stress is a positive way which helps one to improve his/her health. Materials and Methods: This research is a quasi-experimental study with the aim of determining the effect of education of methods of coping with stress on rate of stress among women working at Tehran University of Medical Sciences. After primary study, 138 cases were chosen through census sampling. The collection tool was Chaudron stress scale. The statistical tests included t test and 2. Data were analyzed by SPSS software. Result: The result showed that there was no significant difference between level of stress before and after education in domains of job stress (p=0.22), life health stress (p=0.53), personal life stress (p=0.44) and personality stress (p=0.1). Also the statistical result of X2 did not show significant correlation between variables such as type of school, age, duration of work, marital status, number of children, educational level and housing condition with job stress. Conclusion: The result showed that work environment is an important source of stress for working women. It could have undesirable effects on physical and emotional health of women. It seems that short term education can not decrease the stress of women; therefore it is necessary to organize different long-term education programs, consultation and other strategies to reduce stress.